Determination of ultra-trace levels of palladium in water samples by cloud point extraction and graphite furnace atomic absorption spectrometry. Issue 9 (September 2021) - Han, Quan; Huo, Yanyan; Yang, Xiaohui; Yao, Xing
A highly sensitive method for the determination of ultra-trace levels of palladium in water samples by cloud point extraction and graphite furnace atomic absorption spectrometry is developed. The procedure is based on complexation of palladium with a laboratory-prepared novel chelating agent, 2-(5-bromo-4-methyl-2-pyridylazo)-5-dimethylaminoaniline (5-Br-4-CH3 -PADMA) and subsequent micelle-mediated extraction of the product using the non-ionic surfactant octylphenoxypolyethoxyethanol (Triton X-114) as an extracting agent. Analytical parameters affecting the separation and detection process, such as pH, concentration of the chelating agent and surfactant, equilibration temperature, and time are investigated. The optimized conditions are as follows: pH 6.0 HAc–NaAc buffer solution, 1 × 10 −5 mol L −1 5-Br-4-CH3 -PADMA, and 0.1% (w/v) Triton X-114. Under the optimized conditions, the calibration graph is linear in the range of 0.1–12 ng/mL, the detection limit is 0.05 ng/mL for palladium, and the relative standard deviation is 2.9% ( c = 1.0 ng/mL, n = 10). The enrichment factor, defined as the ratio of the aqueous solution volume to that of the surfactant-rich phase volume after dilution with HNO3 –methanol solution, is 200. The proposed method is applied to the determination of palladium in water samples with satisfactory results.